España Mira al Norte: El Ártico, Operaciones Navales y Cambio Climático (Journal of the Spanish Institute for Strategic Studies, 2024)
The Arctic is increasingly regarded as an arena for power projection. During the last decades, climate change and its effects have been a major driver of change for a region formerly isolated of any international tensions between great powers. As the ice keeps melting away, the traditional “exceptionalism” which characterized the region has vanished almost completely. Russia, aware of the fact that its northern flank now becomes vulnerable with a navigable Arctic, has returned to its abandoned Soviet-era bases, while also holding a fleet of icebreakers which eclipses those of its neighbors. An open Arctic will bring within the possibility of establishing a maritime route shorter and cheaper than the existing one through the Suez Canal. Such possibility, which will end up becoming a reality sooner or later, has made Arctic States and other from afar start investing in their own capabilities so as to be able to participate in such future. Spain, also being aware of this changing reality, must strive to take advantage of its natural maritime predisposition and position itself in a way that it can also benefit from all the advantages and promises that an Arctic free of ice will bring.
Keywords: Arctic; Spain; Climate Change; Naval Operations; Submarine Warfare